2005
DOI: 10.1074/jbc.m500309200
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion-dependent Effects of Clioquinol on the Fibril Growth of an Amyloid β Peptide

Abstract: Although metal ions such as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
143
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(159 citation statements)
references
References 41 publications
(63 reference statements)
15
143
0
1
Order By: Relevance
“…Slow fibril growth was seen at molar ratios of less than 0.6:1 after 2 days, whereas no extension of preformed amyloid material was observed at equimolar ratios (26). In accordance with our current data, the A 1-40 metal ion complexes were nonfibrillogenic in nature and lacked the ability to bind ThT (26). The data presented here makes the important finding that the switch between the two aggregation states is centered at an equimolar Cu 2+ :peptide ratio in the absence of preformed material.…”
Section: Implications For the Aggregation Of A Peptidementioning
confidence: 90%
See 2 more Smart Citations
“…Slow fibril growth was seen at molar ratios of less than 0.6:1 after 2 days, whereas no extension of preformed amyloid material was observed at equimolar ratios (26). In accordance with our current data, the A 1-40 metal ion complexes were nonfibrillogenic in nature and lacked the ability to bind ThT (26). The data presented here makes the important finding that the switch between the two aggregation states is centered at an equimolar Cu 2+ :peptide ratio in the absence of preformed material.…”
Section: Implications For the Aggregation Of A Peptidementioning
confidence: 90%
“…It is possible that even longer time periods (months to years) are required for these morphological changes to occur. It has also previously been demonstrated that Cu 2+ treated A 1-40 dose not support fibril growth by docking to the ends of existing fibrils (26). These results, together with the observation of decreased ThT fluorescence ( Figure 3) and alterations in aggregate morphology (Figures 2), indicate that the Cu 2+ induced aggregates of A 1-42 represent an endproduct from an alternative aggregation pathway that is incapable of subsequent fibril formation on the short (hours) to medium (days) time scale used.…”
Section: Cu 2+ :Peptide Molar Ratio Controls the Aggregation State Ofmentioning
confidence: 94%
See 1 more Smart Citation
“…Clioquinol has a moderate affinity for iron, copper, and zinc (Kd Cu is 1.2×10 -10 M, Kd Zn is 7×10 -8 M) [197], and for this reason it was explored as a drug for AD. Although it was initially considered a chelator [198][199][200][201], it has more recently been characterized as a copper/zinc ionophore, which functions to redistribute these metals into cells [196,[202][203][204][205][206]. Clioquinol is still considered a moderate iron chelator as it has been shown to lower iron levels in animal models of iron overload [64,148,[207][208][209][210], and has not been shown to redistribute iron into cells using ionophore assays.…”
Section: Clioquinol and Pbt2mentioning
confidence: 99%
“…Addition of DFO prior to cathepsin D degradation caused a disappearance of the inhibitory effect by Al on Ab peptides degradation; this suggests that Al exerted its effects via reversible interaction with the Ab peptide. This result also indicates that a chelating agent like Clioquinol [45,46] may be effective for the treatment of Alzheimer's disease, if Al participates in the pathophysiology of the disease. Since these results strongly indicate that Al associated with Ab as soluble complex at pH 4.5, we attempted to determine if a significant amount of Al bound to the peptides using a PVDF membrane technique.…”
mentioning
confidence: 80%